The Concept of Ibn Sina's Educational Thought - Adidarma, Ridha Nestu; Choiriyah, Irma; Darmawan, Dicky; Salsabila, Noni; Suryadi, Rudi Ahmad (UNIVERSITAS PAKUAN, 2025)
Ibn Sina, known in the Western world as Avicenna, was a prominent intellectual figure in the Islamic tradition of the 10th and 11th centuries. His thoughts on education reflect a holistic approach that integrates intellectual, spiritual, and moral dimensions. Ibn Sina perceived education not merely as a process of knowledge transfer but also as a means of character building and the comprehensive development of human potential. This study employs a qualitative method with a historical-descriptive approach to explore the ideas and implementation of Ibn Sina's educational philosophy within the context of Islamic education. The findings indicate that Ibn Sina emphasized the importance of educational objectives, teaching methods, curriculum, and developmental stages of learners. He advocated for a balance between worldly and spiritual knowledge, as well as the alignment of education with children's psychological development. His integrative and progressive ideas have significantly contributed to shaping the paradigm of Islamic education and remain relevant for modern educational systems.